Neutron scattering reveals water confined in a watertight bilayer vesicle - Abuillan, Wasim; Becker, Alexandra S.; Tanaka, Motomu (Journal of the American Chemical Society, 2018)
Water molecules confined in a nanocavity possess distinctly different characteristics from those in bulk, yet the preparation of such nanocavities is still a major experimental challenge. We report here a self-assembled vesicle of an anionic perfluoroalkylated [60]fullerene, unique for its outstanding stability and water tightness, containing water not bound to the membranes. Small-angle neutron scattering revealed that a vesicle of 14 nm outer radius contains a 2 nm thick fullerene bilayer, inside of which is a 3 nm thick membrane-bound water and unbound water in the 4 nm innermost cavity. The vesicle shows astonishingly low water permeability that is 6 to 9 orders of magnitude smaller than that of a lipid vesicle. As a result, a single vesicle isolated on a substrate can retain the interior water in air or even under high vacuum, indicating that the vesicle cavity provides a new tool for physicochemical studies of confined water as well as ions and molecules dissolved in it.